(untitled) (Academic journal Industrial Machine Building Civil Engineering, 2017)
The article is devoted to determining of the thermal reliability rates of CFS wall panels based on three thermo-technical failure criteria - reduced heat transfer resistance, exceeding the values of the temperature difference between the reduced temperature of the inner surface of structure and internal air temperature above the permissible temperature values by the sanitary requirements and criteria of reduction of local values of the inner surface temperature to the temperature of vapor-liquid condensation. With increasing coefficient of variation of thermal conductivity from 2.28% to 20%, the probability of refusal of wall panels of light steel thin-walled structures, under the criterion of the specified heat transfer resistance, is increasing from 9,85´10-7 to 0,015 respectively.